The Eber Hyde Mollusk Collection - James L. Murphy (Hello World!, 1972)
Remnants of the Eber Hyde collection of terrestrial and freshwater mollusks have recently come to light in the Department of Geology collections, Case Western Reserve University. Collected during the latter part of the nineteenth century, much of the material is from Ohio, particularly Fairfield and Scioto counties. Other specomens occur from various localities in the eastern United States, though many of these were presumably acquired by trade. The Hyde Collection provides documentation of several new county records for Ohio, and topotypes of Pleurocera labiatum Lea permit the resolution of the question of that species' identity. It is here considered a junior subjective synonym of Pacutum Rafinesque.